PEMAHAMAN HOLISTIK TENTANG KARMAPHALA DALAM LONTAR TATTWA WIT: PERSPEKTIF FILOSOFIS - Anggy Paramitha Sari (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Hindu society highly believe in the law of cause and effect that also known as karma phala. Every action will produce an equal result. Every single action of each individual has a power to bring happiness or sadness. The law of karma phala tied all of His Creation without exception, fairly and objectively. Karma come from the thoughts, words and actions. Lontar Tattwa Wit is one of lontar (manuscript) that has the explanation about karma phala tenet in it. This article generally aimed to obtain holistic understanding about karma phala in Lontar Tattwa wit based on philosophical perspective.